Quality Evaluation Of Gluten-Free Rice Donut Incorporated With Eggplant Flour And Xanthan Gum - Akesowan, Adisak; Chareonkul, Apinya; Tantakasem, Sirinard (Department of Technology of Agricultural product (THP) Jambi University, 2022)
Incorporating functional ingredients for producing a healthy gluten-free product is necessary to assess the impact on product characteristics and acceptability. This study aimed to determine the effect of eggplant flour and xanthan gum on gluten-free rice donuts. Four donut formulations were prepared by replacing rice flour with 10% and 20% eggplant flour and adding 0.5% and 1% xanthan gum (flour weight basis). The rice donut was the control. Physical properties on specific volume, firmness, and color, as well as sensory evaluation on a 9-point hedonic scale, were investigated. When replacing rice flour with 10% eggplant flour, the donut with 1% xanthan gum showed better specific volume and firmness but was darker and received more acceptable than that with 0.5% xanthan gum. The 20% eggplant flour replacement deteriorated rice donuts’ physical properties and sensory attributes. The preference mapping indicated that the rice donut with 10% eggplant flour and 1% xanthan was the best formulation.